TOURISM PROMOTION OF CHOMDAO RAFTING. A CASE STUDY: BANLANKHOI COMMUNITY, LAN KHOI DISTRICT, PA PHAYOM DISTRICT, PHATTHALUNG PROVINCE THAILAND - Prajam, Woranat; Damrongwattana, Jittima; Dechochai, Udomsak; Khaenamkaew, Daycho (Journal of Humanities and Social Sciences, Songkhla Rajabhat University| jhuso-skru, 2019)
This research study purpose To study the methods of organizing adventure tourism activities, rafting and stargazing In order to study the problems and obstacles in organizing rafting and stopping tourism activities And to study the guidelines for promoting tourist spots, rafting, watching the stars A case study of Ban Lan Khoi community, Lan Khoi subdistrict, Pa Phayom district Phatthalung By using qualitative research methods The research found that Methods of organizing rafting and rafting adventurous tourism activities found that 1) The rafting camps for rafting the stars are of a standard There is a beautiful decoration both inside and outside. Complete with facilities 2) Tourism activities, rafting, watching the stars There are a wide variety of formats, such as those created by operators and adventure rafting activities such as scuba diving, scuba diving, fishing or boat viewing. Which are all water adventure activities that challenge the ability of tourists. 3) The process of rafting to see the stars. The operator explained A safe rafting method for visitors Problems and obstacles in organizing whitewater rafting tourism activities: 1) Many tourists tend to ignore safety regulations, such as not wearing a life jacket, helmet, etc. 2) Seasons will be a major obstacle to rafting. Watching the stars, such as the occurrence of wild floods, etc., etc. 3) is an activity that has advanced competition today. Guidelines for promoting tourist spots and rafting and watching the stars found that 1) Natural resource management Rafting, watching the stars, managing natural resources efficiently In terms of procurement, storage, care and repair Economical use 2) Development of community tourist attractions By government agencies. 3) Disseminating activities through information systems continuously.